On Subscalarity of Some 2 × 2 M-Hyponormal Operator Matrices. (25th February 2014) - Zuo, Fei; Shen, Junli
Abstract : We provide some conditions for2 × 2 operator matrices whose diagonal entries areM -hyponormal operators to be subscalar. As a consequence, we obtain that Weyl type theorem holds for such operator matrices.